Development Of "Kids Learning" Educational Game as A Basic Learning Media about Geometry Materials for Kindergarten Children - Achmad Buchori; Devita Rahmania; Sharifah Osman (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
The purpose of this research is to increase interest in learning for kindergarten children to recognize android-based flat shapes. This is an instructional game with both a learning and a gameplay menu. There are games on the play option such as Remembering Matches, Counting, and Guessing flat shapes using Multimedia. This study employs the Development Life Cycle (MDLC) model. The targets in this study were students of Kindergarten Mardirini Sidogemah Sayung Demak. Data processing was taken from the validation of media, materials, and user questionnaires using a Likert scale in the assessment. The results of the expert validation showed an average of 95% stating that this kid learning product was "Very Eligible" to use. Then user testing was carried out on 20 student respondents, with a percentage of 93%, very happy using this product